Association study between genetic variations in gene and lung cancer risk in North Indian population: A multiple interaction analysis - Charu Bahl; Siddharth Sharma; Navneet Singh; Digamber Behera (Tumor Biology)
Wnt pathway has been implicated in the process of human carcinogenesis. Axis inhibition protein2 ( Axin2 ), a major scaffold protein is an antagonist of Wnt pathway and is potent to act as a tumor suppressor gene in various human cancers. Therefore, the seven polymorphic sites of Axin2 gene were analyzed, in relation to lung cancer susceptibility in North Indians. A total of 608 subjects were genotyped using PCR-RFLP technique for each polymorphic site including 303 cases and 305 controls. Further association analysis was carried out using logistic regression approach to obtain adjusted odds ratio and statistical significance. MDR and CART analysis were applied to evaluate high order interactions between the SNP’s. Three out of seven studied polymorphic sites showed a strong protective effect in subjects having mutant genotype for Axin2 148 C >T and heterozygous genotype for 1365 G > A and 1712 + 19 G > T towards lung cancer risk. The other important finding was the significant association of Axin2 148 C >T in SQCC patients having variant (TT) genotype. Axin2 1712 + 19 G >T showed a decreased risk for all the histological subtypes in patients with heterozygous (GT) genotype. MDR analysis predicted a best interaction model ( Axin2 148, Axin2 2062 and Axin2 1712 +19 ) with maximum CVC (10/10) and minimum prediction error (0.38) along with significant permutation p -value. CART analysis gave a wide spectrum of interactive combinations which exhibited a major contribution in modulating lung cancer susceptibility. Axin2 148 and Axin2 1712 + 19 were found to play a major role in modulating lung cancer risk.